1990
DOI: 10.2307/3869096
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of the Arabidopsis 2S Albumin Genes and the Effect of Increasing Gene Family Size

Abstract: We studied the expression of the four genes encoding 2S albumin seed storage proteins (at2S1 to at2S4) in Arabidopsis thaliana. All four genes followed similar temporal profiles throughout development, but at2S2 and at2S3 were expressed at significantly higher levels than at2S1 or at2S4. In situ hybridization showed that at2S2 to at2S4 mRNAs were present throughout the embryo, whereas at2S1 was expressed at levels similar to at2S2 and at2S3 in the embryo axis but at only insignificant levels in the cotyledons.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 15 publications
6
76
0
1
Order By: Relevance
“…Their regulation might, however, differ slightly from one SSP gene to another because the effects of single mutations on individual genes are not identical. At2S1, for example, is less affected by fus3 or lec2 single mutations than other At2S genes, probably because At2S1 is specifically expressed in the embryonic axis (Guerche et al, 1990) where the effects of the fus3 and lec2 single mutations are the weakest (as judged by At2S3 expression).…”
Section: Fus3 and Lec2 Function Similarly And Differently From Abi3 Imentioning
confidence: 99%
See 2 more Smart Citations
“…Their regulation might, however, differ slightly from one SSP gene to another because the effects of single mutations on individual genes are not identical. At2S1, for example, is less affected by fus3 or lec2 single mutations than other At2S genes, probably because At2S1 is specifically expressed in the embryonic axis (Guerche et al, 1990) where the effects of the fus3 and lec2 single mutations are the weakest (as judged by At2S3 expression).…”
Section: Fus3 and Lec2 Function Similarly And Differently From Abi3 Imentioning
confidence: 99%
“…We wondered whether other SSP genes are regulated in the same way as At2S3. In order to test this, we designed specific probes for four At2S genes and three cruciferin genes (Guerche et al, 1990;Pang et al, 1988) and analysed SSP gene expression in abi3, fus3, lec2 and lec2 fus3 mutants. We found that the expression of all genes was reduced to a variable extend in fus3 and lec2 single mutants but drastically reduced in lec2 fus3 (Fig.…”
Section: At2s3 Expression Is Abolished In Lec2 Fus3 Double Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression patterns of seed protein genes are highly regulated spatially and temporally during seed development Perez-Grau and Goldberg, 1989;Guerche et al, 1990), and resulting storage proteins are processed and targeted to protein bodies (Shotwell and Larkins, 1989). The tissue-specific expression of seed protein genes during seed development has made them especially useful as models of gene expression in embryogenesis, and as a consequence, there have been extensive studies on the structure and expression of these genes from numerous plant species.…”
Section: Seed Protein Gene Regulationmentioning
confidence: 99%
“…The siliques for RNA extraction were harvested during the developmental stages when the expression of endogenous Arabidopsis 2S albumins is highest (between stages D and E, as defined by Guerche et aL, 1990). Total RNA from siliques was extracted and used in slot-blot analysis as described previously .…”
Section: Rna Extraction and Slot-blot Analysismentioning
confidence: 99%